(untitled) (Journal of Fatima Jinnah Medical University, 2024)
Background: ABO and Rh blood groups are associated with the predisposition of several diseases (pancreatic cancer, breast cancer, cardiovascular diseases, obesity, and some psychiatric illness) but their association with BMI is still inconclusive. This study aimed to find any possible correlation between the ABO and Rh blood groups and BMI. Subjects and methods: A cross-sectional descriptive study was conducted, among medical students from the first year to the final year of MBBS at Nishtar Medical University. The slide agglutination method was used to determine the blood groups of study participants. BMI of students was divided into the following categories <18.5kg/m2, 18.5-24.9kg/m2, 25-29.9kg/m2, >30kg/m2. Chi-square test was performed to find the correlation between blood groups and BMI categories of students. One-way-ANOVA test was applied to see any significant difference in BMI (mean) among students with blood groups A, B, AB, and O. Results: A total of 313 students, comprising 152 (48.56%) males and 161 (51.14%) females, with a mean of age 21.75 years and BMI of 22.37 kg/m2 presented an insignificant association between BMI, ABO, and Rh blood groups (p>0.05). The frequency of blood groups was reported as A in 81 (25.88%), B in 124 (39.62%), AB in 33 (10.54%), O in 75 (23.96%), Rh-positive 275 (87.86%), and Rh-negative 38 (12.14). Blood group “B” was found most prevalent: in males 58 (38.2%) and in females 66 (41%). The distribution of BMI categories <18.5kg/m2, 18.5-24.9kg/m2, 25-29.9kg/m2 and >30kg/m2 was reported as 37 (11.82%), 153 (48.89%), 93 (29.71%) and 30 (9.59%) respectively. Conclusion: An insignificant association was found between the BMI and ABO and Rh blood groups. Students with blood groups AB and B were found to have higher mean BMI. Male students showed inclination towards high BMI.